Tingkat Kesadaran Masyarakat Akan Pentingnya Beraktivitas Fisik Selama Pandemi Covid-19 - Vega Soniawan; Aryadie Adnan; Jeki Haryanto; Heru Syarli Lesmana; Ikhwanul Arifan; Eko Purnomo; Dicky Surya Pratama (Universitas Negeri Padang, 2021)
COVID-19 is an infectious disease caused by the corona virus. This virus can be transmitted to other people through droplets from people who have the disease. To prevent the transmission of this virus, people need to do quarantine at their house, self-isolation for those who are infected, and also implementing health protocols and recommendations set by the government. In addition, people can do physical activity to strength and maintain their immune system. Physical activity is an activity that involves the movement of skeletal muscles that requires more energy than the resting phase, and it is important for energy balance in the body. WHO also recommends the people to always keep hygiene and do physical activity to stay healthy. This study aims to determine the level of public awareness toward the importance of physical activity during the pandemic. This research used data analysis method. Researchers conducted direct interviews with residents of RT 003 RW 002, Surau Gadang, Nanggalo District, Padang City. According to the research result, it can be concluded that public awareness is low in doing physical activity to maintain body resistance during the pandemic.